Ask Question
30 June, 23:01

Rewrite the equation in ax^2 + bx+c form: x^2=5

Answers (2)
  1. 30 June, 23:15
    Answer = x² - 5

    All you really have to do is move 5 to the other side, which makes it negative.

    There is no B in this equation ... although technically it is 0.

    If you prefer to write x² + 0x - 5, that's fine.
  2. 30 June, 23:17
    =x2 (1-d) + 5x - (1+d)

    Step-by-step explanation:

    Most of us would call this "combining like terms", which is in fact equivalent to factoring common monomial factors.

    Hopefully you are aware of the distribution property of multiplying over addition: for all a, b, c, a (b+c) = ab+ac. This can be used in reverse to combine like terms: ca+ba = (b+c) a, or perhaps more familiarly with renamed variables, ax+bx = (a+b) x=x (a+b).

    In the given equation, one grouping is made with x2-dx2=1x2-dx2=x2 (1-d). A second grouping is made with - 1-d = - (1+d). You can check these via distribution if you like. Therefore: x2+5x-1-dx2-d=x2-dx2+5x-1-d=x2 (1-d) + 5x - (1+d).
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍 “Rewrite the equation in ax^2 + bx+c form: x^2=5 ...” in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers